(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Ten years passed between the publishing of Virginia Woolf’s first novel, The Voyage Out (1915), and Mrs Dalloway (1925). In the meantime, The Great War broke out, leaving nothing but unprecedented devastation behind. It is in this atmosphere that Woolf started her literary career, finishing her first novel just before the beginning of what was later to be called the First World War, bearing witness to the immediate pre-war ideology. On the other hand, in her later novels, she was to depict the indellible post-war consequences. One such novel, about the shell-shock effect, was Mrs Dalloway. The idea of this paper is to do a literary research into the pre-war atmosphere, and post-war consequences, depicted in the two novels by Virginia Woolf, аn author also known as a feminist-oriented pacifist. One of her best-known war-affected characters stands out in the world literature of our day – Septimus Warren Smith. It is through this character’s eyes that we are going to experience the horrors of the Great War.